Conference Report: Third Qualitative Research Encounter - Martínez Labrín, Soledad; Bivort Urrutia, Bruno; Orellana Fonseca, Cristian; Vásquez Rivas, Claudia; Opazo Vega, Dámaris; Paredes, Juan Pablo (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2013)
This report gives an account of the main topics discussed during the Third Qualitative Research Encounter, framed within the work of the Research Group: Gender, Citizenship, and Equity [Investigación Género, Ciudadanía y Equidad] at the University of Bio-Bio, Chile. The event centered on the thematic axis that gives the group its name: gender, citizenship and equity. At the same time, each axis was subdivided, resulting in the formation of three panels, with presentations of qualitative research carried out in Chile (in addition from other South American countries and Spain). We present the main themes of discussion and the main conclusions each group arrived in each axis and panel. Finally, we appreciate the activity as a whole, including its projections for a next event. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs140131